2021
DOI: 10.1108/sajm-05-2021-0070
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Binge-Watching on Netflix during the COVID-19 pandemic

Abstract: PurposeThe purpose of the study is to dive into various binge-watching habits of Netflix users amidst the COVID-19 pandemic. Consumers find themselves amidst the COVID-19 lockdown with more free time to indulge in these viewing habits. This study investigates motivational factors, amount of media consumption and negative attributes associated with binge-watching on Netflix during the COVID-19 outbreak.Design/methodology/approachThis study has employed an exploratory research design and obtained primary data vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…Digital entertainment also offers users a new mode of media consumption (Granow et al, 2018), and this supports the notion that entertainment will drive people to binge-watching (Arditi, 2021;Gangadharbatla et al, 2019;Sadana & Sharma, 2021). Moreover, Rahman and Arif (2021), expressed that a wide range of shows available on Netflix for entertainment purposes incline viewers to engage in binge-watching behaviour during the Covid-19 pandemic. This also supports the study by Kumar et al, (2021), who found that entertainment was the most dominating motive to influence binge-watching during the Covid-19 pandemic.…”
Section: Hypothesis Developmentmentioning
confidence: 63%
See 2 more Smart Citations
“…Digital entertainment also offers users a new mode of media consumption (Granow et al, 2018), and this supports the notion that entertainment will drive people to binge-watching (Arditi, 2021;Gangadharbatla et al, 2019;Sadana & Sharma, 2021). Moreover, Rahman and Arif (2021), expressed that a wide range of shows available on Netflix for entertainment purposes incline viewers to engage in binge-watching behaviour during the Covid-19 pandemic. This also supports the study by Kumar et al, (2021), who found that entertainment was the most dominating motive to influence binge-watching during the Covid-19 pandemic.…”
Section: Hypothesis Developmentmentioning
confidence: 63%
“…The outcome of this research is aligned with the research done by Panda and Pandey (2017) which indicates that students perform binge-watching due to the entertainment value generated through the channels of streaming services. In addition, Sadana and Sharma (2021) discovered that young consumers bingewatched their favourite channels for entertainment purposes to relieve themselves from stress, particularly during the Covid-19 lockdown time (Rahman & Arif, 2021). Arditi (2021) also found that the entertainment value creates the cognitive response by allowing the consumers to binge-watch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, products containing robots and similar artificial intelligence have been mostly demanded by people to reduce contact with surfaces. Movie theater closures and curfews have doubled the time adults spend on streaming services daily compared to pre-pandemic times (Rahman & Arif, 2021). In the study conducted in November 2020 to examine the consumption behavior of consumers in Turkey, the majority of the participants stated that the time they spend on surfing the Internet, spending time with family members, shopping online and watching visual content at home has increased (Hacıalioğlu & Sağlam, 2020).…”
Section: Consumer Purchasing Behavior In the Covid-19mentioning
confidence: 99%
“…In this section, the data is collected about the devices used by Netflix subscribers and their satisfaction by studying the number of subscribers obtained in the above table. Afterwards, it is concluded that more Netflix subscribers are more concerned about portability, and these subscribers are generally satisfied with Netflix [6][7][8].…”
Section: Introductionmentioning
confidence: 99%